Optimization of mobile phase composition in simulated moving bed chiral separation processes - Ribeiro, António E. (2011)
This work will present two case studies; the chiral separation of ketoprofen and flurbiprofen enantiomers, both important examples of non-steroidal anti-inflammatory drugs (NSAIDs), frequently used in the treatment of arthritis and related diseases. A complete methodology concerning experimental, modeling and simulation results will be presented, including the enantiomers solubility and adsorption isotherm measurements, fixed-bed and SMB operations. The main focus will be placed on optimizing the mobile phase composition for chiral separation by SMB operation. These two comparative case studies will reveal that there are no predictive general rules for the optimization of mobile phase composition at a production scale and that an individualized study must be carried out, since compounds of the same family (profen enantiomers) can lead to different solutions.